Traditional Chinese medicine treatment strategies for primary dysmenorrhea - Duan, Wenwen; Chen, Dan; Li, Dan; Zeng, Yue; Liu, Shanshan; Huang, Zubo; Wang, Chao; Zhou, Hao (Frontiers in Endocrinology, 2025)
Primary dysmenorrhea is a common disease in women. China, under the influence of their philosophical wisdom, has developed unique theories of common clinical disorders and corresponding therapeutic cultural practices, including the application of unique medical wisdom to the treatment of primary dysmenorrhea. The article reviews the current Traditional Chinese medicine treatment strategies for primary dysmenorrhea, including acupuncture, moxibustion, acupoint application, diet improvement, and lifestyle adjustment. This article also analyzes the benefits and potential mechanisms of these treatments. Finally, this study highlights future directions for dysmenorrhea treatment, including ongoing research and potential new treatment modalities. This review aims to guide healthcare providers in developing the personalized treatment strategies for patients with primary dysmenorrhea and promote a more harmonious doctor-patient relationship.